3D Reconstruction Model of an Extra-Abdominal Desmoid Tumor: A Case Study - Marinozzi, Franco; Carleo, Francesco; Novelli, Simone; Di Martino, Marco; Cardillo, Giuseppe; Petrella, Lea; Bini, Fabiano (Frontiers in Bioengineering and Biotechnology, 2020)
In recent years, Three-Dimensional Reconstruction (3DR) models have become a standard tool in several medical fields such as education, surgical training simulation, patient-doctor communication, and surgical planning. Post-oncologic reconstructive surgery in thoracic diseases might benefit from 3DR models; however, limited data on this application have been published worldwide. In this paper, the aim was to report our experience with 3DR modeling to determine resection and plan the surgical reconstruction in a patient with a desmoid tumor of the chest wall. For a better understanding of the case study, we describe all the steps from acquiring computed tomography (CT) scans to the final 3D rendering. A 68-year-old, non-smoking man presented at our outpatient department with painless swelling of the right anterobasal chest wall. A thorax-abdomen-brain CT scan revealed homogenous solid tissue with a dense mass measuring 80 mm x 62 mm. The final 3D model was evaluated by the surgical team (three medical doctors), who found the model to be powerful. Based on the results and the accuracy of the model, the multidisciplinary team decided that the tumor was resectable. Consequently, a surgical plan based on the 3D model was developed to perform chest wall reconstruction after radical resection. The patient underwent right anterolateral thoracotomy at the seventh intercostal space which confirmed the CT scan findings and revealed infiltration of the serratus muscle and medial portion of the diaphragm. A radical tumor en-bloc resection with chest wall and diaphragm resection was performed. The full-thickness chest wall and diaphragm defects were reconstructed using two separate biologic patches of a porcine dermal collagen implant (PermacolTM Surgical Implant). Postoperative X-ray revealed unremarkable findings; the patient had an uneventful recovery and was discharged six days after surgery. This case study illustrates that 3DR models enable a personalized approach to the treatment of desmoid tumors. Therefore, this approach should be developed further and studied systematically.